“Confirma fratres tuos”. Alle origini del magistero autoritativo del vescovo di Roma (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Il tema - 2. La data di celebrazione della Pasqua - 3. I lapsi e il re-battesimo - 4. La Chiesa di Roma custos fidei et unitatatis; giustificazione storica e dottrinale - 5. Le stesse fonti patristiche nella valutazione di teologi ortodossi contemporanei - 6. Una riflessione conclusiva.“Confirma fratres tuos”. At the origins of the authoritative magisterium of the bishop of RomeABSTRACT: The essay deals with the historical and doctrinal justification of the Church of Rome custos fidei et unitatatis in the sub-apostolic age, about the doctrine of the faith through its positions in about the date for the celebration of Easter, to readmission to the Church of the lapsi, to the re-baptism. The importance of these patristic sources is also given by being held present in the theses of contemporary orthodox theologians.